Phytoremediation using different concentrations of lead acetate pb(ch3coo)2.3h2o by Canavalia ensiformis (jack beans) - Oliveira, Luísa Helena dos Santos; Souza, Camila Miranda de; Marin Pedro, Juliana (Revista Hipótese, 2017)
Canavalia ensiformis(Jack beans) was evaluated as a phytoremediation agent for soils contaminated with lead. Soil was used as soil in PET bottles, contaminated with lead acetate in different concentrations (0, 350, 1,200, 2,400 mg.kg-1). The plant accumulated higher concentrations of lead in the root, and an increase in the accumulation of metal in the species the higher the concentration, and it can be inferred that it has potential as a phytoremediate of lead.
Keywords: phytoremediation; Canavalia ensiformis; jack beans; lead